2012
DOI: 10.5056/jnm.2012.18.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Irritable Bowel Syndrome and Restless Legs Syndrome: A Comparative Study With Control Group

Abstract: Background/AimsAs a common gastrointestinal (GI) disorder, irritable bowel syndrome (IBS) has been reported to be associated with some psychological and neurological factors. This study aimed to evaluate the prevalence rate of restless legs syndrome (RLS) in a sample of IBS patients and to compare this prevalence with that of matched healthy controls.MethodsThis prospective comparative study was conducted in Tehran, Iran during 2010-2011. Based on the Rome III criteria, a total number of 225 definite IBS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…Moreover, changes in the small intestinal bacterial overgrowth (SIBO)-related inflammatory mediator impaired communication between enteric and central nervous system are reported as the pathogenetic mechanisms [5]. A couple of studies have suggested that sleep disorders, particularly restless legs syndrome (RLS), are possible comorbidities in IBS patients [6, 7]. According to the previous studies, nearly 25%–30% of IBS patients experience RLS [68].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, changes in the small intestinal bacterial overgrowth (SIBO)-related inflammatory mediator impaired communication between enteric and central nervous system are reported as the pathogenetic mechanisms [5]. A couple of studies have suggested that sleep disorders, particularly restless legs syndrome (RLS), are possible comorbidities in IBS patients [6, 7]. According to the previous studies, nearly 25%–30% of IBS patients experience RLS [68].…”
Section: Introductionmentioning
confidence: 99%
“…A couple of studies have suggested that sleep disorders, particularly restless legs syndrome (RLS), are possible comorbidities in IBS patients [6, 7]. According to the previous studies, nearly 25%–30% of IBS patients experience RLS [68].…”
Section: Introductionmentioning
confidence: 99%
“…RLS occurs with increased frequency during the course of several systemic inflammatory diseases. 5 11 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, intensity of discomfort and abdominal pain are more common in patients with IBS and RLS. (16) The prevalence of RLS in patients with other gastrointestinal disorders, such as coeliac disease or Crohn's disease, was found to be 25% and 30%, respectively. (17,18) However, only a few studies with small sample sizes have examined the prevalence of autonomic dysfunction in patients with RLS.…”
Section: Introductionmentioning
confidence: 99%
“…(12) More studies have investigated the prevalence of RLS among patients with autonomic complaints and IBS. (13)(14)(15) A prospective comparative study by Borji et al (16) found a significantly higher prevalence of RLS among patients with IBS (25%). Furthermore, intensity of discomfort and abdominal pain are more common in patients with IBS and RLS.…”
Section: Introductionmentioning
confidence: 99%